Exposure of Apis mellifera (Hymenoptera: Apidae) colonies to imidacloprid impairs larval development, promotes oxidative stress in pupae, and induces changes in the midgut of adult bees - Daiani Rodrigues Moreira; Tuan Henrique Smielevski de Souza; Douglas Galhardo; Cinthia Leão Figueira; Samara Calvi Baulli; Breno Gabriel da Silva; Francieli das Chagas; José Washington Santos Oliveira; Jean Samel Rocha; Angélica de Souza Khatlab; Eliane Gasparino; Vagner de Alencar Arnaut de Toledo; et al. (Biological Research)
Abstract Bees are essential pollinators that contribute to maintaining biodiversity and increasing agricultural production. However, by foraging on agricultural crops, bees may become contaminated with compounds used for pest control. In this study, we exposed bee (Apis mellifera L.) colonies to the insecticide imidacloprid (IMD) under field conditions to assess the occurrence of oxidative stress in larvae and pupae and investigate morphological changes in the fat body and midgut of larvae and midgut of adult bees. The apiary area was divided into three groups: control, commercial formulation containing IMD (Evidence® 700WG) (IMDCF), and IMD active ingredient (Sigma–Aldrich) (IMDAI). Treatment groups were fed syrup containing 1 µg L−1 IMD, whereas the control group was fed syrup only. Compared with the control, larvae exposed to IMDCF or IMDAI for 42 days exhibited morphological changes in the external body, midgut, and fat body. The midgut of adult bees contaminated with IMDCF showed only structural remnants of the peritrophic membrane and absence of regenerative cell nests. Oxidative stress analyses revealed that IMDCF-exposed larvae had higher nitrite and carbonylated protein contents and lower catalase and superoxide dismutase activity than control individuals. In pupae, IMDAI decreased catalase activity while increasing superoxide dismutase activity. These findings indicate that IMD has the potential to significantly impact the development of bees and their colonies by disrupting vital organs responsible for normal physiological functioning and overall activities of individuals. Oxidative stress, which was detected at different stages of bee development, may induce lipid, protein, and DNA oxidation, leading to cell death. Graphical Abstract